Faktor yang Memengaruhi Persepsi Petani dalam Usahatani Kapulaga di Kecamatan Cilongok Kabupaten Banyumas - Nurdiani, Ulfah; Karim, Akhmad Rizqul; Mandamdari, Alpha Nadeira; Sukmaya, Syahrul Ganda (Universitas Galuh, 2025)
The increase in production and productivity of cardamom plants is a continuous effort by the Banyumas Regency Government. One of the efforts made is through a cardamom development program. Farmers' perceptions of cardamom farming are a crucial factor in the development of cardamom, as they can influence the decision to engage in farming. This research aims to: (1) understand farmers' perceptions of cardamom farming, and (2) identify the factors influencing farmers' perceptions of cardamom farming. The study was conducted in July 2024 in Sambirata Village, Cilongok District. A total of 40 cardamom farmers were selected as research respondents. Primary data were collected through observations and interviews using a prepared questionnaire. Secondary data were gathered from various sources, literature, and records related to the research. The data were processed and analyzed descriptively to determine the level of perception and using multiple linear regression analysis to identify the factors influencing perceptions. The results of the research indicate that the overall level of farmers' perceptions of cardamom farming in Banyumas Regency falls into the good category, with a percentage of 77.71%. Factors influencing farmers' perceptions of cardamom farming include age, formal education, number of family dependents, farming experience, and institutional support. Meanwhile, perceptions are not influenced by non-formal education and income (Sig value <0.05).